Risk evaluation of metro tunnel shield construction based on game variable weight extension cloud theory - Xiaowen Sun; Lirong Wu; Dun Wu (Scientific Reports)
Abstract To address the issues of fuzziness and randomness in risk evaluation for subway shield construction, this study proposes a risk assessment model integrating variable weight theory and an extension cloud model to enable a more scientific and effective evaluation. Firstly, the WBS-RBS (Work Breakdown Structure-Risk Breakdown Structure) method was employed to establish a risk evaluation index system for metro tunnel construction, with risk levels classified into Grades I-V. Secondly, the ordinal relationship method (G1) and entropy weight method were applied to calculate the fixed weights of the evaluation indexes. The comprehensive fixed weights are determined based on the game theory, considering the dynamic changes of the evaluation indexes, and the optimal dynamic, comprehensive weights are calculated based on this combined with the variable weight theory. Finally, comprehensive affiliation degrees were obtained through the extension cloud model, and the comprehensive evaluation grade was determined according to the principle of maximum affiliation. The model was applied to the submarine tunnel section of Qingdao Metro Line 8. The results indicate that the risk level of the project is Grade III, which aligns with the actual construction conditions. This consistency validates the rationality and feasibility of the proposed method, offering a novel approach to guide safety management and risk decision-making in metro tunnel construction projects.